Growth and water relations of riparian poplar forests under pressure in Central Asia's Tarim River Basin. (21st February 2020) - Thomas, Frank M.; Lang, Petra
Abstract: The riparian forests in the Tarim Basin (NW China) are mainly composed of poplar species ( Populus euphratica, Populus pruinosa) . In the hyper‐arid climate of this region, the trees are phreatophytes, which rely on access to groundwater. Essential ecosystem services (ESS) of these forests comprise provisioning, regulating, and cultural services. The ESS of the forests are threatened by overuse and a continuous decrease in the groundwater level due to excessive use of water for agriculture, which resulted in a severe reduction of the poplar forest area during the past decades. Studies revealed that the wood of the forests could be sustainably used through a moderate harvesting intensity. Rejuvenation of the forests from seeds is only possible after sediment deposition and wetting of the soil surface upon flooding and at relatively short distances to the groundwater. At sites with larger groundwater distances, trees can only regenerate vegetatively through root suckers emerging from underground root spacers. With increasing distance from the water table, the stands become older and sparser and, ultimately, are doomed to die off. The research results can contribute to develop suitable management schemes for the conservation and protection of Central Asia's riparian forests. The lower reaches of the Tarim River have been subjected to a water release programme for the past 20 years. We recommend focusing the diversion of such additional ("ecological") water to stands with a short distance to the groundwater to keep these forests fully functional and to maintain their ability to regenerate from seeds.